Platelets in the NETworks interweaving inflammation and thrombosis - Wienkamp, Ann-Katrin; Erpenbeck, Luise; Rossaint, Jan (Frontiers in Immunology, 2022)
Platelets are well characterized for their indispensable role in primary hemostasis to control hemorrhage. Research over the past years has provided a substantial body of evidence demonstrating that platelets also participate in host innate immunity. The surface expression of pattern recognition receptors, such as TLR2 and TLR4, provides platelets with the ability to sense bacterial products in their environment. Platelet α-granules contain microbicidal proteins, chemokines and growth factors, which upon release may directly engage pathogens and/or contribute to inflammatory signaling. Additionally, platelet interactions with neutrophils enhance neutrophil activation and are often crucial to induce a sufficient immune response. In particular, platelets can activate neutrophils to form neutrophil extracellular traps (NETs). This specific neutrophil effector function is characterized by neutrophils expelling chromatin fibres decorated with histones and antimicrobial proteins into the extracellular space where they serve to trap and kill pathogens. Until now, the mechanisms and signaling pathways between platelets and neutrophils inducing NET formation are still not fully characterized. NETs were also detected in thrombotic lesions in several disease backgrounds, pointing towards a role as an interface between neutrophils, platelets and thrombosis, also known as immunothrombosis. The negatively charged DNA within NETs provides a procoagulant surface, and in particular NET-derived proteins may directly activate platelets. In light of the current COVID-19 pandemic, the topic of immunothrombosis has become more relevant than ever, as a majority of COVID-19 patients display thrombi in the lung capillaries and other vascular beds. Furthermore, NETs can be found in the lung and other tissues and are associated with an increased mortality. Here, virus infiltration may lead to a cytokine storm that potently activates neutrophils and leads to massive neutrophil infiltration into the lung and NET formation. The resulting NETs presumably activate platelets and coagulation factors, further contributing to the subsequent emergence of microthrombi in pulmonary capillaries. In this review, we will discuss the interplay between platelets and NETs and the potential of this alliance to influence the course of inflammatory diseases. A better understanding of the underlying molecular mechanisms and the identification of treatment targets is of importance to increase patients’ survival and clinical outcome.